2017
DOI: 10.1111/irv.12493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data sources and approaches for estimation of influenza‐associated mortality in India

Abstract: BackgroundNo estimates of influenza‐associated mortality exist for India.ObjectiveTo evaluate national mortality and viral surveillance data from India for assessing their appropriateness in estimating influenza‐associated mortality using varied analytic approaches.MethodsWe reviewed influenza virus surveillance data from a national influenza surveillance network. We also reviewed national mortality data from Civil Registration System (CRS), Medical Certification of Cause of Death (MCCD) and the Sample Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Estimating influenza mortality is complicated by the fact that influenza is often not listed as underlying cause on death certificates, thus influenza-associated mortality estimation is often conducted using indirect estimation methods with statistical modeling [5,6]. These indirect methods rely on national vital records systems as well as consistent surveillance data, which has also hampered many estimates in LMICs such as India due to issues with the quality or availability of necessary data sources [6][7][8]. However, estimates from the lower resource and tropical climate settings can be important to understand the true burden of influenza on high risk age groups and populations.…”
Section: Viewpoints Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating influenza mortality is complicated by the fact that influenza is often not listed as underlying cause on death certificates, thus influenza-associated mortality estimation is often conducted using indirect estimation methods with statistical modeling [5,6]. These indirect methods rely on national vital records systems as well as consistent surveillance data, which has also hampered many estimates in LMICs such as India due to issues with the quality or availability of necessary data sources [6][7][8]. However, estimates from the lower resource and tropical climate settings can be important to understand the true burden of influenza on high risk age groups and populations.…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…The SRS is a routine annual demographic survey, serving as the primary system for collecting data on births and deaths in India since 1971. Details of the SRS, including design, sampling scheme, physician assignment of the underlying cause of death and the methodology have been described elsewhere [8,16,17]. In brief, the SRS divided each state or union territory of India into one million sample units based on the population using the 2001 census.…”
Section: Mortality Data: Sample Registration System (Srs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in this Special Edition, from India and South Africa, evaluated various data sources and methods and determined the best approaches for developing disease burden estimates in their country. The study from India found that while the Sample Registration System provided the most appropriate national mortality data set, other mortality data sources could be used for subregional estimates . The South African study showed that weekly proportion and influenza subtype‐specific proxies provided the best model fit with non‐significant differences in the estimates …”
Section: New Series Of Burden Studiesmentioning
confidence: 99%
“…The outcomes also varied across studies. The most common outcomes were deaths attributable to influenza, used in nine studies, and severe acute respiratory infections (SARI) or its equivalent, used in eight studies . Another seven studies measured excess or absolute hospitalizations due to influenza, and five studies measured community or outpatient visits .…”
Section: New Series Of Burden Studiesmentioning
confidence: 99%